2000
DOI: 10.1016/s0370-2693(00)00805-4
|View full text |Cite
|
Sign up to set email alerts
|

Chaplygin-like gas and branes in black hole bulks

Abstract: We explore the possibility to locate a brane in black hole backgrounds. We study explicitly the cases of BHTZ and Schwarzschild-anti de Sitter (AdS) black holes. Our result is that branes cannot be supported by brane tension alone and it is necessary to introduce other forms of matter on the brane. We find classes of perfect fluid solutions obeying to peculiar state equations. For the case of BHTZ bulk geometry the state equation takes exactly the form of a "Chaplygin gas", which is relevant in the brane conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 12 publications
1
72
0
Order By: Relevance
“…The most obvious candidate of dark energy is the cosmological constant [3]. In addition, many other cosmological models such as the quintessence [4], the Chaplygin Gas [5], the braneworld models [6], the Cardassian models [7] are proposed to explain the accelerating expansion of the Universe. Recently, Cohen et al [8] suggested the holographic dark energy model to reconcile the breakdown in quantum field theory caused by the conflict between the effective field theory and the so-called Bekenstein entropy bound [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The most obvious candidate of dark energy is the cosmological constant [3]. In addition, many other cosmological models such as the quintessence [4], the Chaplygin Gas [5], the braneworld models [6], the Cardassian models [7] are proposed to explain the accelerating expansion of the Universe. Recently, Cohen et al [8] suggested the holographic dark energy model to reconcile the breakdown in quantum field theory caused by the conflict between the effective field theory and the so-called Bekenstein entropy bound [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Interesting examples are the generalized Chaplygin gas [15] and the condensate cosmology [16]. These are all motivated by unifying dark energy and dark matter to one dark fluid in the early universe.…”
Section: A Modelsmentioning
confidence: 99%
“…Certain effects in deformable solids, of stripe states in the context of the quantum Hall effect and of other phenomena, can be explained by the negative pressure arising from the CG EoS [18]. It is also useful when studying the stabilization of branes in black hole bulks [19][20][21]. A microscopic description of CG suggests that it can be regarded (phenomenologically) as the effect of the immersion of our four-dimensional world into some multidimensional bulk [22,23].…”
Section: Introductionmentioning
confidence: 99%